Oversharing dan Resiko Phishing: Tinjauan Perilaku Bermedia Sosial Mahasiswa di Salatiga - Angga Prastiyo; Widodo, Tri; Avrilida, Era Zaher; Widyanti, Agnes (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2025)
ABSTRACT The rapid growth of social media has transformed how individuals communicate and manage personal information, while also creating space for oversharing that is often carried out without a clear awareness of its risks. Oversharing opens opportunities for digital crimes such as phishing, especially when users, including university students, fail to manage their privacy boundaries properly. This study aims to analyze how students’ oversharing practices on social media increase their vulnerability to phishing by using Communication Privacy Management (CPM) theory as the main framework, particularly through the concepts of boundary rules, co-ownership, and boundary turbulence. This research adopts a descriptive qualitative approach with a constructivist paradigm and involves 40 informants from four universities in Salatiga. Data were collected through in-depth interviews and analyzed using thematic analysis. The findings show that most students understand the idea of oversharing, yet they continue to engage in it for social recognition and self-expression. Many of them do not have clear boundary rules in deciding who can access their personal information and to what extent it can be shared, which leads them to unintentionally disclose sensitive data such as location, identity, and daily routines.Once personal information has been shared and becomes co-owned by others, weak coordination over how that information is used can trigger boundary turbulence, creating opportunities for data misuse in the form of phishing. Theoretically, this study reinforces the relevance of CPM in explaining students’ digital privacy management; practically, it underscores the importance of digital literacy and stronger privacy policies in higher education settings. ABSTRAK Perkembangan media sosial telah mengubah cara individu berkomunikasi dan mengelola informasi pribadi, sekaligus membuka ruang bagi fenomena oversharing yang sering kali tidak disadari risikonya. Oversharing menciptakan peluang bagi tindakan kriminal digital seperti phishing, terutama ketika batas privasi tidak dikelola dengan baik oleh pengguna, termasuk mahasiswa. Penelitian ini bertujuan menganalisis bagaimana praktik oversharing mahasiswa di media sosial meningkatkan kerentanan terhadap phishing dengan menggunakan teori Communication Privacy Management (CPM) sebagai kerangka utama, khususnya melalui konsep boundary rules, co-ownership, dan boundary turbulence. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan paradigma konstruktivisme, melibatkan 40 informan dari empat perguruan tinggi di Kota Salatiga. Data dikumpulkan melalui wawancara mendalam dan dianalisis menggunakan analisis tematik. Hasil penelitian menunjukkan bahwa sebagian besar mahasiswa memahami konsep oversharing, tetapi tetap melakukannya demi pengakuan sosial dan ekspresi diri. Banyak dari mereka belum memiliki boundary rules yang jelas dalam menentukan siapa yang boleh mengakses informasi pribadi dan sejauh mana informasi tersebut dibagikan, sehingga secara tidak sadar mengungkapkan data sensitif seperti lokasi, identitas, dan kebiasaan sehari-hari. Ketika informasi pribadi telah dibagikan dan menjadi co-ownership dengan orang lain, lemahnya koordinasi penggunaan informasi memicu boundary turbulence yang membuka peluang penyalahgunaan data dalam bentuk phishing. Secara teoretis, penelitian ini menegaskan relevansi CPM dalam menjelaskan pengelolaan privasi digital mahasiswa serta secara praktis, menyoroti pentingnya literasi digital dan penguatan kebijakan privasi di lingkungan perguruan tinggi.